2005
DOI: 10.1103/physrevlett.95.067001
|View full text |Cite
|
Sign up to set email alerts
|

Rabi-Type Oscillations in a Classical Josephson Junction

Abstract: We study analytically and numerically the phase-modulation properties of a classical Josephson tunnel junction biased in the zero-voltage state and phase locked to an external ac field. We show that the phase-locked state is being modulated in the transients, or in response to perturbations, and the modulation frequency is calculated as a function of relevant system parameters, such as microwave field amplitude. Our analysis demonstrates that the modulation of a phase-locked state in an entirely classical Jose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 13 publications
9
60
0
Order By: Relevance
“…For example, it has been demonstrated that the multipeak switching distributions as a function of varying system bias for a constantly applied microwave field can be understood as classical high-Q resonances in the nonlinear system [14,17]. Also Rabi-type oscillations in the switching statistics of Josephson systems perturbed by microwave pulses have been shown to be consistent with theoretical and numerical expectations based on a classical model of a Josephson junction, which exhibit the transients in response to the pulsed perturbations [18,19]. It is the purpose of this paper to demonstrate that Ramsey-type fringes can also be observed in the classical model when the recipe of the experimental measurements is followed.…”
Section: Introductionmentioning
confidence: 86%
“…For example, it has been demonstrated that the multipeak switching distributions as a function of varying system bias for a constantly applied microwave field can be understood as classical high-Q resonances in the nonlinear system [14,17]. Also Rabi-type oscillations in the switching statistics of Josephson systems perturbed by microwave pulses have been shown to be consistent with theoretical and numerical expectations based on a classical model of a Josephson junction, which exhibit the transients in response to the pulsed perturbations [18,19]. It is the purpose of this paper to demonstrate that Ramsey-type fringes can also be observed in the classical model when the recipe of the experimental measurements is followed.…”
Section: Introductionmentioning
confidence: 86%
“…Dashed line shows the linear dependence expected for a two-level system. Continuous line is the quantum prediction taking into account the multilevel process, dotted line the classical model[17]. The vertical dotted line indicates the anharmonicity strength: ν 01 − ν 12…”
mentioning
confidence: 99%
“…In the present paper we have chosen to keep the same terminology ͑Rabi-type oscillations, Ramseytype fringes, etc.͒ introduced in the thesis and in the papers which inspired it. [25][26][27][28] Other authors have recently reported on RCSJ-based analysis of the three-junction Josephson system presenting their own terms and analysis. 38 In these papers, the pumping by an ac drive was used in order to generate low frequency modulations of phase and energy, and the conclusions confirm a nonlinear phenomenon reported previously in simulations and experiments; [25][26][27]39 namely, that it is possible to phase-lock Josephson systems by superharmonic pumping.…”
Section: Discussionmentioning
confidence: 99%